A Defense Against Quine's Attack on Analyticity - Carrasco, David (My University, 1970)
This thesis is an attempt to rescue the analytic-synthetic distinction from the attacks of W.V.O. Quine ,and his followers. In particular, the notion of synonymy in natural languages is examined along with a critical discussion of attempts to define this notion. Also, Carnap's explication of logical truth is discussed to some length with emphasis on semantical rules, meaning postulates, and state-descriptions.
Keywords: Philosophy; Philosophy